2019
DOI: 10.1088/1361-6501/ab1b09
|View full text |Cite
|
Sign up to set email alerts
|

Correction of phase errors due to leakage currents in wideband EIT field measurements on soil and sediments

Abstract: Electrical impedance tomography (EIT) is a promising method to characterize important hydrological properties of soil, sediments, and rocks. The characterization is based on the analysis of the phase response of the complex electrical conductivity in a broad frequency range (i.e. mHz to kHz). However, it is challenging to measure the small phase response of low-polarizable soils and rocks in the higher frequency range up to 10 kHz. In order to achieve the required phase accuracy in the kHz frequency range, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
(11 reference statements)
0
22
0
Order By: Relevance
“…Recently, methods have been presented for modelling-based removal of both inductive and capacitive coupling, for borehole applications (Zhao et al 2013), cross-hole applications (Zhao et al 2014) and surface measurements (Zimmermann et al 2016;Kang & Oldenburg 2017). All these methods require an accurate knowledge of the cable relative positions for the removal of the inductive coupling, and fan-like cable layouts have been proposed for surface applications (Zimmermann et al 2016). This limits the actual usability of the correction in the field considerably, especially when electrode distances bigger than 1 m are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, methods have been presented for modelling-based removal of both inductive and capacitive coupling, for borehole applications (Zhao et al 2013), cross-hole applications (Zhao et al 2014) and surface measurements (Zimmermann et al 2016;Kang & Oldenburg 2017). All these methods require an accurate knowledge of the cable relative positions for the removal of the inductive coupling, and fan-like cable layouts have been proposed for surface applications (Zimmermann et al 2016). This limits the actual usability of the correction in the field considerably, especially when electrode distances bigger than 1 m are used.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, low-noise sequences with nested dipoles, like the gradient array, are still very difficult to use in big-scale field FD applications. Furthermore, Zimmermann et al (2016) points out that you actually need a model-dependent correction, which takes the leakage current and the total parasitic capacity between system ground and the soil into account.…”
Section: Discussionmentioning
confidence: 99%
“…Dahlin and Zhou 2006;Flores-Orozco et al 2013;Kelter et al 2018). Correction methods for capacitive and inductive coupling effects have also been developed for borehole (Zhao et al 2013(Zhao et al , 2015, and surface FDIP measurements (Zimmermann et al, 2019), but have not yet been transferred to commercially available measurement equipment.…”
Section: F R O M T H E L a B O R A T O R Y T O T H E F I E L D S C A L Ementioning
confidence: 99%
“…Laboratory studies have demonstrated the sensitivity of SIP measurements to changes in temperature above the freezing point (e.g., Binley et al, 2010;Zisser et al, 2010) and in frozen samples (e.g., Kemna et al, 2014a;.…”
mentioning
confidence: 99%
“…The main challenge regarding the conduction of field SIP measurements corresponds to the contamination of the data at frequencies above 1 Hz by electromagnetic (EM) coupling (e.g., Flores Orozco et al, 2021;Pelton et al, 1978;Zimmermann et al, 2019). EM coupling may result in self-induction of the near subsurface materials, cross-talking between cables, and the https://doi.org/10.5194/tc-2021-234 Preprint.…”
mentioning
confidence: 99%